As French as everyone else? : a survey of French citizens of Maghrebin, African, and Turkish origin - Brouard, Sylvain (Temple University Press, 2011)
France is often depicted as the model of assimilationist or republican integration in the international literature on immigration. However, rarely have surveys drilled down to provide individual responses from a double representative sample. In As French as Everyone Else?, Sylvain Brouard and Vincent Tiberj provide a comprehensive assessment of the state of integration in France and challenge the usual crisis of integration by systematically comparing the "new French" immigrants, as well as their children and grandchildren born in France, with a sample of the French general populatio.